Prevention of acute myocardial infarction by nurses at a family clinic in Realengo, Rio de Janeiro (Research, Society and Development, 2022)
Objective: To identify the prevention of acute myocardial infarction through the nurses of a family clinic in the west of Rio de Janeiro. Methodology: Qualitative field research carried out in a Basic unit with nurses, one preceptor and eight nursing residents, Opinion No.: 4,876,209. Results They reported the low frequency of consultations during the Covid-19 pandemic, It was observed the autonomy that the nurse has in relation to monitoring and prescription according to the programs of the Ministry of Health, It was seen that throughout the period of the pandemic, the care of chronic users, was being done by spontaneous demand through the renewal of recipes and there was a reduction in care and permanent education activities, due to the contingency and sanitary restrictions in the health unit, due to COVID 19, there were also some practices non-pharmacological to users in relation to food and care. Conclusion: The continuing education activity takes place in this family clinic, and nurses are involved in health programs and related education activities, but in this period of Pandemic due to the accumulation of calls, illness of professionals, occurrence of immunization and exams to detect COVID 19, there were no continuing education activities.